2010
DOI: 10.1345/aph.1m288
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus: A New Mammalian Target of Rapamycin Inhibitor for the Treatment of Advanced Renal Cell Carcinoma

Abstract: Based on a review of the currently available literature, everolimus provides a safe and efficacious treatment option for patients with renal cell carcinoma who have progressed on treatment with sunitinib and/or sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It is possible that destruction to the kidney's tubules and interstitium stemming from RCC [26], may contribute to dysfunctional reabsorptive processes and concomitant hyperglycemia. In addition, while the role that the kidney plays in the excretion of everolimus is minor [27], the majority of RCC patients in our study had undergone nephrectomies [2], raising the possibility of impaired renal elimination of everolimus. The mechanisms underlying the unfavorable hyperglycemic outcomes seen in this study remain unclear and undoubtedly necessitate further study.…”
Section: Discussionmentioning
confidence: 84%
“…It is possible that destruction to the kidney's tubules and interstitium stemming from RCC [26], may contribute to dysfunctional reabsorptive processes and concomitant hyperglycemia. In addition, while the role that the kidney plays in the excretion of everolimus is minor [27], the majority of RCC patients in our study had undergone nephrectomies [2], raising the possibility of impaired renal elimination of everolimus. The mechanisms underlying the unfavorable hyperglycemic outcomes seen in this study remain unclear and undoubtedly necessitate further study.…”
Section: Discussionmentioning
confidence: 84%
“…Inhibition of mTOR has been demonstrated to suppress liver tumor growth and metastasis (9,10). Several clinical and preclinical studies have demonstrated that the mTOR inhibitor rapamycin and its analogues can be used to treat various types of solid tumor, including esophageal squamous cell carcinoma (11), lung cancer (12), renal cell carcinoma (13) and prostate cancer (14). Therefore, the mTOR pathway may be a prospective target for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…68 To date, only 1 study has been published that examined the efficacy and safety of TT in patients with mRCC requiring HD. Masini and colleagues conducted a retrospective study of 24 patients with mRCC who were treated with sunitinib (16 patients) or sorafenib (8 patients).…”
Section: Discussionmentioning
confidence: 99%